2019
DOI: 10.20546/ijcmas.2019.808.313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytetracycline-dosing on the Growth, Safety and Intestinal Histology of Nile Tilapia, Oreochromis niloticus (L.) Juveniles

Abstract: The present study was carried out to evaluate the effect of oxytetracycline (OTC)dosing at five different concentrations, viz., 0 mg (0X), 80 mg (1X), 240 mg (3X), 400 mg (5X) and 800 mg (10X) kg -1 biomass day -1 for 30 consecutive days on the growth, safety and intestinal histology of Nile tilapia, Oreochromis niloticus (L.) juveniles. The OTC-residues in the edible muscle were detected at scheduled intervals by LC-MS/MS. A dose-dependent decline in feed intake, biomass and survival were recorded in OTC-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
5
10
0
Order By: Relevance
“…(1.99-2.03 times) followed by 5X (2.03-2.11 times) groups. The signi cant dose-dependent differences in the fold increase in the biomass of Nile tilapia among the dosing groups indicated that OTC at the higher doses may affect the growth so also in an earlier study with similar doses for 30 days dosing (Julinta et al 2019a). The 0.5X-dose had signi cantly high growth increment, while the therapeutic dose (1X) did not affect the growth of Nile tilapia.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…(1.99-2.03 times) followed by 5X (2.03-2.11 times) groups. The signi cant dose-dependent differences in the fold increase in the biomass of Nile tilapia among the dosing groups indicated that OTC at the higher doses may affect the growth so also in an earlier study with similar doses for 30 days dosing (Julinta et al 2019a). The 0.5X-dose had signi cantly high growth increment, while the therapeutic dose (1X) did not affect the growth of Nile tilapia.…”
Section: Discussionmentioning
confidence: 68%
“…Our results agree with Trushenski et al (2018), who recorded 3% mortality in Nile tilapia fed with 80 mg OTC/kg biomass/day for 10 days. Julinta et al (2019a) also recorded increased mortalities with the increase in OTC-dose, i.e., from 5.00±0.00% in 1X to 13.33±2.89% in 10X groups, respectively when fed for 30 consecutive days. The observations like pale kidney and liver, discolouration and liquefaction of internal organs at the higher doses (3X-10X groups) possibly indicated the consequence of toxicity upon long-term oral OTC-dosing that might have triggered the mortality.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Resistance to third-generation cephalosporins (cefalexin) is known to be associated with the derepression of chromosomal enzymes (Zdanowicz et al, 2020) and anthropogenic Aeromonas infections (Igbinosa et al, 2012). Oxytetracycline resistance was comparatively less as the change in strains' resistance depends on seasonal variation rather than medication (Julinta et al, 2019). The AMR of Aeromonas samples exhibited against fluoroquinolones (ciprofloxacin and enrofloxacin) and sulfonamides (cotrimoxazole, sulfafurazole and trimethoprim) were analogous with the studies of…”
Section: Antibiotic Sensitivitymentioning
confidence: 74%
“…The incorporation rate of OTC was calculated to deliver an approximate dosage of 0 mg, 80 mg and 800 mg OTC/kg biomass/day for 10 consecutive days. The control and OTCdiets were prepared by top-coating the commercial feed with appropriate amounts of OTC in 5 mL vegetable oil separately as described in Julinta et al (2019) to administer doses of 0, 80 and 800 mg/kg biomass/day when fed at 6% BW/day. The control diet was prepared without medication but coated with vegetable oil to minimize variation between the feeds.…”
Section: Oxytetracycline (Otc) Medicated Diets Preparationmentioning
confidence: 99%